(untitled) (CIPEEX, 2022)
ABSTRACT (OU RESUMO): ADOLESCENCE IS AN INTERMEDIATE STAGE BETWEEN CHILDHOOD AND ADULTHOOD. THIS STAGE IS MARKED BY UNCERTAINTIES, REBELLIOUSNESS, IMPULSIVITY, AS WELL AS PHYSICAL, SOCIAL, MENTAL, EMOTIONAL AND SEXUAL CHANGES. THE YOUTH FEEL THE WEIGHT OF SOCIETY ON REACHING THEIR EXPECTATIONS, OFTEN IMPOSED, CLOSING IN THIS WAY, BEFORE THE COMMUNITY. FACED WITH THIS SEA OF €‹€‹CHANGES, THE DENTAL SURGEON HAS A GREAT RESPONSIBILITY TO CALL ATTENTION TO ORAL HEALTH EDUCATION ACTIONS, AIMING AT THE INTEGRALITY OF CARE. IT IS THUS NECESSARY TO OVERCOME THIS BARRIER. THE GOAL OF THE ROTARY DONANA SOCIAL ACTION WAS TO BREAK PARADIGMS, BRINGING THE TEENAGER’S AWARENESS TO ORAL HYGIENE, STIMULATING SELF-CARE. ORAL HEALTH PROMOTION AND PREVENTION ACTIONS WERE CARRIED OUT BY MEANS OF SUPERVISED BRUSHING WITH THE BRUSHSTROKES OF THE DENTAL COURSE OF UNIEVANGELICA, AS WELL AS DONATION OF BRUSHES. THE TARGET AUDIENCE WAS THE STUDENTS OF THE ROTARY DONANA STATE COLLEGE OF THE MUNICIPALITY OF ANÁPOLIS, BETWEEN THE SIXTH AND NINTH YEAR. THESE ACTIONS ARE OF PARAMOUNT IMPORTANCE, OFTEN AS A SOLUTION HYPOTHESIS, AIMING AT THE CREATION OF CONTINUOUS ORAL HEALTH PROGRAMS FOR THIS AGE GROUP, STIMULATING THEM TO BE MODIFYING AGENTS OF SOCIETY.&NBSP; KEYWORDS: ADOLESCENT. ORAL HYGIENE. COMMUNITY PARTICIPATION.